Thickness‐Dependent Energy‐Level Alignment at the Organic–Organic Interface Induced by Templated Gap States. Issue 3 (17th December 2021) - Hagenlocher, Jan; Broch, Katharina; Zwadlo, Matthias; Lepple, Daniel; Rawle, Jonathan; Carla, Francesco; Kera, Satoshi; Schreiber, Frank; Hinderhofer, Alexander
Abstract: Planar organic heterostructures are widely explored and employed in photovoltaic cells, light‐emitting diodes, and bilayer field‐effect transistors. An important role for device performance plays the energy level alignment at the inorganic–organic and organic–organic interfaces. In this work, incremental ultraviolet photoelectron spectroscopy measurements and real‐time X‐ray scattering experiments are used to thoroughly investigate the thickness‐dependent electronic and structural properties of a perfluoropentacene (PFP)‐on‐[6]phenacene heterostructure. For both materials an incremental increase of the material work function (positive interface dipole) is found. For [6]phenacene, this can be assigned to a thickness‐dependent change of molecular arrangement evident from a change of the unit cell volume and a consequential alteration of the ionization energy. In the case of PFP the interface dipole stems from charge transfer from the substrate into unoccupied molecular orbitals resulting in an electrostatic potential on the surface. The magnitude of this potential can be correlated with an increased gap state density resulting from templated structural defects mediated by the bottom layer. Abstract : The energy‐level alignment at inorganic/organic and organic/organic interfaces is of fundamental importance for device functionality and efficiency. Combining real‐time X‐ray scattering techniques and incremental ultraviolet photoelectron spectroscopy, structural parameters can be connected to electronic properties in prototypical heterostructures dependent on film thickness. The data suggests that additional electronic states resulting from structural defects are a key factor controlling the energy‐level alignment.